Public Service Quality in Watumalang District Office of Wonosobo Regency With Servqual Method - Aqillah Rifqi Azizah; Anis Susanti (Jurnal Kebijakan Publik, 2025)
This research focuses on the implementation of service quality at the Watumalang District Office of Wonosobo Regency using the SERVQUAL method where this method will measure service quality from five dimensions, namely Tangibles, Responsiveness, Reability, Assurance, and Emphaty. This research uses a descriptive qualitative approach with data collection through interviews and observations. The data obtained was then analyzed using the Miles and Huberman method to find out how the implementation of service quality with the help of NVIVO software. The results showed that in the Tangibles dimension it is necessary to improve facilities and infrastructure to support the implementation of services, in the responsiveness dimension it has been carried out well the officer has implemented responsiveness and a good attitude when providing services, in the reliability dimension it has also been implemented well the officer has reliability when providing services as well as the assurance dimension has also been implemented well the officer has been able to provide reliable service guarantees to the community while in the Empathy dimension it is necessary to improve facilities for pregnant women and people with disabilities.